Axis manipulation to solve Inverse Kinematics of Hyper-Redundant Robot in 3D Space - Sheldon Ijau Winston; Annisa Jamali (Journal of Integrated and Advanced Engineering (JIAE), 2022)
A solution based on inverse kinematics is required for the robot's end effector, also known as its tip, to reach a target. Current methods for solving the inverse kinematics solution for a hyper-redundant robot in three 3D are generally complex, difficult to visualize, and time-intensive. This requires the development of new algorithms for solving inverse kinematics in a quicker and more efficient manner. In this study, an axis manipulation using a geometrical approach is used. Initially, a general algorithm for a 2 m-link hyper-redundant robot in 3D is generated. The method employed a repetitive basic inverse kinematics solution of a two-link robot on virtual links. The virtual links are generated using a specific geometric proposition. Finally, the 3D solution is generated by rotating about the global z-axis. This method reduces the mathematical complexity required to solve the inverse kinematics solution for a 2-m-link robot. In addition, this method can manage variable link manipulators, thereby eliminating singularity. To demonstrate the effectiveness of the model, numerical simulations of hyper redundant models in 3D are presented. This new geometric approach is anticipated to enhance the performance of hyper-redundant robots, enabling them to be of greater assistance in fields such as medicine, the military, and search and rescue.